2016
DOI: 10.1016/j.amepre.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Dissemination of Evidence-Based Interventions for HIV Prevention

Abstract: In 1999, IOM issued a report that recommended that the Centers for Disease Control and Prevention should disseminate evidence-based HIV prevention interventions (EBIs) to be implemented by health departments, community-based organizations, drug treatment centers, and clinics. Based on these recommendations, the Diffusion of Effective Behavioral Interventions Project was initiated in 2000 and began disseminating interventions into public health practice. For 15 years, the Centers for Disease Control and Prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…While efforts are arguably being made to improve the reporting of interventions (e.g. through the TIDieR checklist [ 96 ]), this is a fairly recent development, and many EBIs, such as DEBIs, do not always include sufficient descriptions of intervention components [ 90 ]. Also, simply reporting on intervention components is not enough; efforts must also be made to consider whether, and if so, how, different components can be effectively adapted to different contexts and populations [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…While efforts are arguably being made to improve the reporting of interventions (e.g. through the TIDieR checklist [ 96 ]), this is a fairly recent development, and many EBIs, such as DEBIs, do not always include sufficient descriptions of intervention components [ 90 ]. Also, simply reporting on intervention components is not enough; efforts must also be made to consider whether, and if so, how, different components can be effectively adapted to different contexts and populations [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Blueprints for Violence Prevention, 22 National Registry of Effective Programs and Practices (www.nrepp.samhsa.gov), CDC's Effective Interventions: HIV Prevention that Works (www.effectiveinterventions.org; Collins et al 23 ), and the National Cancer Institute's Research-Tested Intervention Programs (http://rtips.cancer.gov/rtips/index.do) are repositories of evidence-based preventive interventions available for the settings and populations that have relevant behavioral health needs. How does the field harness all of this local implementation (and likely adaptation) to learn more about the effectiveness and optimization of the evidence-based practices than would ever be possible through efficacy and effectiveness trials?…”
Section: Advancing the Science Of Intervention Adaptationmentioning
confidence: 99%
“…Low value Around 2006 the Centers for Disease Control and Prevention disseminated a suite of evidence-based behavioral HIV prevention interventions to local organizations (Collins & Sapiano, 2016;Johns et al, 2016). Due to continued investment in biomedical research, pre-and postexposure prophylaxis (PreP and PEP) have demonstrated such high efficacy that it is now more cost-effective to provide PreP and PEP to those who are at highest risk for HIV rather than provide behavior change interventions to a more general population (Holtgrave, 2010).…”
Section: Hiv Interventionsmentioning
confidence: 99%